PVA/chitosan biofilms enriched with biosynthesized silver nanoparticles and tea tree oil: Towards multifunctional and environmentally friendly materials - Karatas, Mukaddes; Erzen, Buket; Aydogmus, Ercan; Orhan, Ramazan (Elsevier, 2025)
This study aims to investigate the synergistic effects of biosynthesized silver nanoparticles (AgNPs) and tea tree oil (TTO) (0, 3, 5, and 7 wt%) on enhancing the functional properties of polyvinyl alcohol/chitosan (PVA/CS) nanobiofilms. The structural, morphological, mechanical, thermal, and physicochemical properties of the films were analyzed using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), mechanical tests, thermal conductivity, dielectric constant, swelling, and water solubility studies. FTIR analysis confirmed the successful incorporation of AgNPs and TTO, while SEM images revealed structural differences between silver nanoparticles synthesized using basil extract (B-AgNPs) and silver nanoparticles synthesized using bay leaf extract (BL-AgNPs), with BL-AgNPs-based films exhibiting a denser and more uniform morphology. TTO incorporation significantly influenced the dielectric properties, thermal conductivity, and water absorption behavior of the films, reducing their swelling ratio and enhancing their hydrophobicity. The biodegradation results demonstrated that the films containing 3 wt% TTO exhibited the highest degradation rates (up to 62.90 % after 21 days), indicating enhanced environmental sustainability. Research indicates that PVA/CS biofilms doped with TTO and enhanced with AgNPs, produced using eco-friendly techniques, show great promise as biodegradable substitutes for food packaging and wound dressing applications.
Keywords: Nanobiofilms; Tea tree oil; Green synthesis; Silver nanoparticles; Food packaging